2010
DOI: 10.1016/j.jacc.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of High-Dose Dobutamine Stress Magnetic Resonance Imaging in 1,493 Consecutive Patients

Abstract: DS-MRI can accurately identify patients who are at increased risk for cardiac death and myocardial infarction, separating them from those with normal findings, who have very low risk for future cardiac events. (Prognostic Value of High Dose Dobutamine Stress Magnetic Resonance Imaging; NCT00837005).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 27 publications
(18 reference statements)
5
53
2
2
Order By: Relevance
“…[20][21][22][23]26,30 Of the 13 series of patients included for subanalysis using the criterion to define the test as negative, 7 used the absence of inducible PDs [20][21][22]27,[29][30][31] as the criterion to define a negative test; of these studies, 1 used dipyridamole as the stressor, 4 used adenosine, and 2 used a stress protocol with both dipyridamole and adenosine. In the remaining 6 series of patients, the definition of a negative study was based on the absence of inducible ; of these, 1 used dipyridamole and 5 used dobutamine as the stressor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23]26,30 Of the 13 series of patients included for subanalysis using the criterion to define the test as negative, 7 used the absence of inducible PDs [20][21][22]27,[29][30][31] as the criterion to define a negative test; of these studies, 1 used dipyridamole as the stressor, 4 used adenosine, and 2 used a stress protocol with both dipyridamole and adenosine. In the remaining 6 series of patients, the definition of a negative study was based on the absence of inducible ; of these, 1 used dipyridamole and 5 used dobutamine as the stressor.…”
Section: Resultsmentioning
confidence: 99%
“…Data from 1 study were not considered for subanalysis because information related to PDs and WMAs could not be separated. 26 In this study, dobutamine was used as the stressor. Eight of the 14 included studies reported rates of myocardial revascularization and UA in addition to major coronary events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Существует независимая связь между неблагопри-ятными сердечно-сосудистыми исходами при много-факторном анализе у пациентов с положительным результатом МРТ сердца с добутамином и бессобы-тийной выживаемостью >99% у пациентов без при-знаков ишемии на протяжении 36-месячного пери-ода наблюдения [200]. Имеются подобные данные по перфузионной МРТ сердца с аденозиновой нагруз-кой [201].…”
Section: стресс-мрт сердцаunclassified
“…In a direct comparison, 3.0 T MPI-MR was found to be superior to 1.5 T MPI-MR for the detection of FFR-positive lesions [44]. In 1493 patients with known or suspected CAD, a negative dobutamine stress MR was associated with a <0.5 % 4-year event rate in patients with a low or intermediate pre-test probability of CAD [45]. However, the 4-year event rate in patients with a negative dobutamine stress MR but a high pre-test probability or with known CAD was still 5 % [45].…”
Section: Comparison With Ffrmentioning
confidence: 94%